Turnin' it up a notch: how spillovers from foreign direct investment boost the complexity of South Africa's exports - Bjørn Bo Sørensen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Countries' economic complexity, and the associated diversification and sophistication of their exports, is a key determinant of economic growth. Understanding how South African firms learn to export more sophisticated products is, therefore, an important policy issue. Using administrative data covering the entire tax-paying population of firms in South Africa, we argue that foreign direct investment can stimulate export upgrading in manufacturing firms. We find that the level of sophistication of the most complex product exported by local firms increases in tandem with the presence of multinational enterprises located in upstream, supplying sectors within the same province. The study is the first within the associated literature to (i) provide firm-level evidence of export upgrading induced by foreign direct investment in Africa, (ii) employ the fitness algorithm to measure export complexity, and (iii) detect spillover effects from foreign direct investment materializing at the top line of domestic firms' export basket.
Keywords: C38; D22; F61; O31; 330; economic complexity; foreign direct investment (FDI); spillovers; export upgrading; manufacturing; South Africa